PENGARUH EXPERIENTIAL MARKETING DAN PERSEPSI KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA RM KHAS SUNDA MANG ENGKING JUANDA DI JAWA TIMUR - Siti Puti Fauziah Hilman; Novi Marlena (Management Insight: Jurnal Ilmiah Manajemen, 2020)
The purpose of this study was to determine consumer satisfaction The Mang Engking Juanda Sidoarjo Gubug East Java based on the influence of experiential marketing and perceived service quality. This type of research is a quantitative descriptive. The sampling technique used is non-probability sampling with a purposive sampling method. The sample used was 126 respondents. The results of this study indicate that the experiential marketing variable has a positive and partially significant effect on customer satisfaction of 4.307> 1.979 with a significance value of 0.000 <0.05. Variable perception of service quality has a positive and partially significant effect on customer satisfaction by 4.598> 1.979 significance value 0.000 <0.05. Experiential marketing variables and perceived service quality positive and significant simultaneous effect on customer satisfaction at the Mang Engking Juanda Sidoarjo Governor's Office at 119.102> 3.07 with a significance value of 0.000 <0.05.